Prevalence of anxiety and depression among students appearing for NEET examination in a rural and urban area of Tamil Nadu: a cross sectional analytical study - Marimuthu, Janakiram; P., Lavanya; Grace, D. Lavanya (International Journal Of Community Medicine And Public Health, 2022)
Background: Mental health problems can reduce the quality of student’s life by affecting their academic achievement and physical health. Higher education being a prerequisite for a successful future, the NEET exams have been the source of stress and anxiety for several students. The aim of the study was to determine the prevalence of anxiety and depression among students facing NEET exams and their associated factors. Methods: This was a cross-sectional analytical study design. The sample size is 150 (75 each in rural and urban area). Results are presented as proportion and Chi-square test was done to assess the association of the factors to adherence. Results: Among the 150 students, the prevalence of anxiety among urban students was 40% whereas the prevalence of anxiety among rural students was 60% and the prevalence of depression among urban students was 45.3% whereas the prevalence of depression among rural students was 56%. There was statistical association between gender, school issues, family issues, socio-economic status, and anxiety and depression. Conclusions: More than one-third of the students had anxiety and more than half of the participants had depression. The mental health status of the students should be taken into consideration by the teachers, students, and the government while the students appear for the NEET examination.